2019
DOI: 10.1037/pag0000379
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes and historic differences in narcissism from adolescence to older adulthood.

Abstract: In the debate about whether or not narcissism has been increasing in recent history, there is a lack of basic information about how narcissism changes across the adult lifespan. Existing research relies on cross-sectional samples, purposely restricts samples to include only college students, or follows one group of individuals over a short period of time. In the current study, we addressed many of these limitations by examining how narcissism changed longitudinally in a sample of 747 participants (72.3% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 87 publications
(163 reference statements)
0
43
1
Order By: Relevance
“…Participants ( N = 348, 78% women) in this study were young people ( M = 19.27 years ( SD = 1.61, Range = 17–25)), see Table 1 . We targeted persons in late adolescence (16–18 years) and emerging adulthood (18–25 years) to recruit our sample and used the definition of young people for this age period [ 7 , 17 , 73 , 76 ]. A snowball method of recruitment was used, where notices for the study were provided to young people who had finished high school and were contemplating study at university.…”
Section: Methodsmentioning
confidence: 99%
“…Participants ( N = 348, 78% women) in this study were young people ( M = 19.27 years ( SD = 1.61, Range = 17–25)), see Table 1 . We targeted persons in late adolescence (16–18 years) and emerging adulthood (18–25 years) to recruit our sample and used the definition of young people for this age period [ 7 , 17 , 73 , 76 ]. A snowball method of recruitment was used, where notices for the study were provided to young people who had finished high school and were contemplating study at university.…”
Section: Methodsmentioning
confidence: 99%
“…Once narcissists have obtained leadership positions and are negatively affecting their followers, other measures should be taken to minimize negative outcomes. Being a relatively stable personality trait that decreases slightly over the life span and in reaction to life events (Chopik and Grimm 2019;Grosz et al 2019;Wetzel et al 2019), narcissism in itself is hardly affected by training programs or coaching. This can be attributed to narcissists being resistant to critical feedback about themselves (Bushman and Baumeister 1998;Kernis and Sun 1994).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Using parent and teacher reports, they found that interpersonal callousness was stable across a 9‐year interval, from childhood to adolescence. The study of Zuckerman and O’Loughlin (2009) on American students revealed that narcissism is stable across 6 months and Chopik and Grimm (2019) provided further support of this stability across the life span. Bloningen, Hicks, Krueger, Patrick, and Iacono (2006) also revealed that psychopathic traits of fearless dominance are stable, the impulsive antisociality decreases from late adolescence to early adulthood.…”
Section: Current Studymentioning
confidence: 97%